Effectiveness of the sexual attitude restructuring curriculum amongst Taiwanese graduate students. Issue 2 (4th March 2018) - Lin, Yi-Li; Lin, Yen-Chin
Abstract: This article discusses the effectiveness of the Sexual Attitude Restructuring (SAR) curriculum in developing positive sexual attitudes amongst Taiwanese graduate students in human sexuality. Through purposive sampling, 32 graduate students in human sexuality were selected to participate in the study. Before and after providing participants with a 16-week SAR curriculum, the Sexual Attitude Scale and focus group interviews were used for data collection using a quasi-experimental design. Findings indicate that the SAR curriculum led to positive changes in students' attitudes. This change was especially significant for those who had more conservative or negative sexual attitudes. A thematic analysis of the interview transcripts shows that the students saw their attitudes towards sexuality changing due to the desensitisation, sensitisation and integration effects of the learning activities. Based on these findings, recommendations are made for further studies and the use of SAR curriculum as part of the education of sexuality and health professionals.